Detection of Human Remain Using GPR Technique - Attar, Hassan A.; Alwan, Haidar A.; Abdulkareem, Ahmad O.; Jabbar, Rasheed H.; Hannoon, Ryadh A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, animal bones with different shapes and sizes were used to study the characteristics of the ground penetrating Radar system wares reflected by these bones. These bones were buried underground in different depths and surrounding media. The resulting data showed that the detection of buried bones with the GPR technology is highly dependent upon the surrounding media that the bones were buried in. Humidity is the main source of signal loss in such application because humidity results in low signal-to-noise ratio which leads to inability to distinguish between the signal reflected by bones from that reflected by the dopes in the media such as rock .